2019
DOI: 10.1136/bmjopen-2019-029793
|View full text |Cite
|
Sign up to set email alerts
|

Mortality trends of liver diseases in mainland China over three decades: an age-period-cohort analysis

Abstract: ObjectiveTo analyse mortality trends of liver diseases in China over the past 30 years.DesignAge-period-cohort analyses were applied to liver diseases data obtained from the Chinese Health Statistics Annual Report (1987–2001) and the Chinese Health Statistics Yearbook (2003–2017).SettingGeneral population in mainland China.OutcomesMortality rates and age, period and cohort effects on three categories of liver diseases: primary liver cancer (PLC), chronic liver disease and cirrhosis (CLD), and viral hepatitis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…All of these can compound the prevalence of MCI. The true cohort effect can only be revealed through future studies using a method that can separate the effects of age, cohort, study period, and other confounding factors [ 138 ]. At this stage, the interpretation and application of the pooled results of this systematic review should be cautious.…”
Section: Discussionmentioning
confidence: 99%
“…All of these can compound the prevalence of MCI. The true cohort effect can only be revealed through future studies using a method that can separate the effects of age, cohort, study period, and other confounding factors [ 138 ]. At this stage, the interpretation and application of the pooled results of this systematic review should be cautious.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, older age was identified as an independent risk factor for advanced disease in the GZ phase of CHB 9 . Given the absence of hepatic inflammation and HBV‐specific T‐cell response before 30 years old 27 and that the mortality risks of HCC, chronic liver disease, and cirrhosis significantly increase with age over 30 years old, 28 age > 30 years was used in our subgroup analyses, and the results also support that age > 30 years with ALT exceeding the new thresholds (ALT >27 U/L for males and ALT >24 U/L for females) is a risk factor of SLHC in GZ CHB patients. Previous studies have shown liver damage in CHB patients with normal ALT levels and HBV DNA ≥2000 IU/mL 20,29 .…”
Section: Discussionmentioning
confidence: 99%
“…In a large US cohort study of 8,539 patients with chronic HBV infection followed up for 12 years, 317 developed HCC, age and family history were independent risk factors for HCC in patients without cirrhosis, and the OR was 32.9 ( 21 ). A study based on the Chinese Health Statistics Yearbook on the relative risk of HBV-related death suggested that the risk of HCC was significantly higher in patients >30 years old ( 22 ).…”
Section: Discussionmentioning
confidence: 99%